The method of chatter suppression in end milling operation - Amin, A. K. M. Nurul; Mohd, Ahmad Azhari; Hadi, Abdul Qayyum (2011)
Various methods of chatter suppression have been introduced to control chatter during machining processes. In this research an innovative approach of chatter suppression during end milling operation using ferrite magnet is being proposed. Design of experiment has been conducted using the Response Surface Method (RSM). The effect of application of magnet was assessed using two response parameters, namely, amplitude and surface roughness. It has been observed that magnetic force within the area of cutting process substantially reduced the chatter (intensive vibration) and improved the surface roughness.